1989
DOI: 10.1002/j.1552-4604.1989.tb03315.x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Beta‐Blockers: Influence of Body Fat on Their Kinetics and Cardiovascular Effects

Abstract: Beta-blockers are among the most widely used antihypertensive drugs. They differ from each other in regard to several factors such as: beta-agonist activity, beta 1-selectivity and solubility. Aim of this work was to evaluate the influence of obesity on the kinetics and the antihypertensive effect of two Beta-blockers with different solubility such as: the water-soluble, atenolol and the liposoluble, metoprolol. The study was carried out according to an open randomized cross-over design. Eight obese hypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 24 publications
1
10
0
2
Order By: Relevance
“…The results of pharmacokinetic studies for the healthy controls were similar to those reported by other investigators [11][12][13]. In obese subjects both with and without hyperlipidaemia the pharmacokinetics of propranolol and atenolol were altered, most significantly during the elimination phases.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The results of pharmacokinetic studies for the healthy controls were similar to those reported by other investigators [11][12][13]. In obese subjects both with and without hyperlipidaemia the pharmacokinetics of propranolol and atenolol were altered, most significantly during the elimination phases.…”
Section: Discussionsupporting
confidence: 87%
“…Nevertheless, the results of Galletti et al [11] suggested that obesity did not influence the pharmacokinetics of water-soluble b-blockers.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Unfortunately, the pharmacokinetics of antihypertensive drugs have not been studied systematically in obese patients. Obesity has been shown to influence the pharmacokinetics of the lipophilic compound metoprolol without affecting the water-soluble compound atenolol [48]. However the antihypertensive effect seemed not to be influenced.…”
Section: What Is the Value Of Gfr Estimation Using Serum Creatinine (mentioning
confidence: 99%
“…Obwohl bisher nur wenige diesbezügliche Studien vorliegen, wurden diese Überlegungen bestätigt in einer Studie mit Verapamil, in der bei Adipösen im Vergleich zu Normgewichtigen ein deutlich höheres Distributionsvolumen und eine verlängerte Eliminationshalbwertszeit gemessen wurden [2]. Das gleiche Phänomen wurde unter dem lipophilen Betarezeptorenblocker Metoprolol beschrieben, während der hydrophile Betablocker Atenolol in den pharmakokinetischen Eckdaten unbeeinflusst blieb [21]. Während jedoch in der ersten Studie intravenös verabreichtes Verapamil in seiner Wirkung, d.h. seiner Pharmakodynamik, durch den Fettanteil beeinflusst wurde, war dies bei Metoprolol nicht zu beobachten; sowohl Metoprolol als auch Atenolol wirkten bei norm-und über-gewichtigen Hypertonikern insgesamt weitgehend identisch blutdrucksenkend.…”
Section: Pharmakokinetische Und Pharmakodynamische Aspekteunclassified